Quality of semen in the reproductive cycle of Cachara (Pseudoplatystoma fasciatum) raised in captivity - Rodrigo Diana Navarro; Juliana Ventorim Lemos; Marcela Tosta Ribeiro (Acta Scientiarum. Biological Sciences, 2019)
In this study, we evaluated the semen quality of Cachara (Pseudoplatystoma fasciatum) raised in captivity during its reproductive period. For the evaluation of qualitative parameters, we analyzed: sperm morphology, sperm motility, and sperm vigor; while for the quantitative parameter, we analyzed sperm concentration. In general, the main significant difference was found in March, with a motility rate of 40% and a duration of 39 seconds. The highest mean concentration (1.2x10⁸) was observed in February, as well as the highest percentage of defects in the intermediate part of the spermatozoa (59%). The morphological analysis of spermatozoa showed an average of 24.2% abnormalities in the head and 22.7% in the intermediate part of spermatozoa of P. fasciatum for the four months studied. We did not find any evident relationship between the climate changes evaluated and the qualitative and quantitative parameters. The greatest difference between the percentage of normal spermatozoa and the sharp increase of defects in the intermediate piece, observed in February, can be explained by the sudden climate change, with a significant decrease in temperature and relative humidity, and increase in precipitation. These findings demonstrate the importance of maintaining an optimum climate interval during the breeding season for P. fasciatum.